A Collaborative Planning Forecasting and Replenishment (CPFR) Maturity Model - Payam Parsa; Mohammad A. Shbool; Tanvir Sattar; Manuel D. Rossetti; Edward A. Pohl Pohl (International Journal of Supply Chain Management, 2020)
This paper presents the development of a framework that organizations can use to assess their CPFR maturity. The proposed modeling framework identifies important functional and structural aspects of CPFR processes and formulates a method for evaluation on a variety of characteristics of CPFR. This paper uses a variant of multi-objective decision analysis to structure the framework into a hierarchical model for CPFR maturity assessment. Each area of the model was identified based on standardized, industry-accepted process definitions. Then, easy to answer questions were formulated to develop a multi-attribute assessment and scoring of capabilities. This model provides a structured representation of the CPFR process for maturity assessment and provides a path of progress for improving the state of CPFR within the  underperforming areas. The developed model can be used by engineering managers for assessing an on-going CPFR program across several areas and communicating the identified high impact improvement areas with various segments of the organization.